O. V. Popova, N. A. Prikhodko, A. Spasskaja. Concatenation of grammatical and lexical components in the political discourse of the USA. - O. V. Popova; N. A. Prikhodko; A. Spasskaja (Philological Treatises, 2020)
The article is devoted to the research of grammatical and lexical components in the political discourse of the USA, their concatenation and interdependence within the discourse. As lexical so grammatical characteristics of the political discourse of the USA serve to achieve the prime goal of the political discourse – to manipulate the electorate, thus to make theatrical performance for the recipients, i.e. the same electorate. The objective of this research is not only to find the principal lexical and grammatical characteristics of the political discourse of the USA, but also to prove their correlation and interdependence while molding the very political discourse to achieve its key goal – theatre reflecting social needs and corresponding these needs. Besides addressing the strategy of theatre in the political discourse of the USA, the research is directed to the detection of the chief morphological and syntactic features of this strategy as an instrument for stylistic organization of the text belonging to the political discourse of the USA. To carrying out the given objectives there are certain methods used in the research: lexical-grammatical analysis, syntactic analysis, stylistic analysis, pragmatic analysis. The article is written within the research topic “Mechanisms of Civil Society Influence upon Euro-Integration Processes in Ukraine” №15.01.10-02.16/18.ЗП.